Biopolymers in diabetic wound care management: A potential substitute to traditional dressings. (8th May 2023) - Hasan, Sara; Hasan, Muhammad Amish; Hassan, Muhammad Umair; Amin, Muhammad; Javed, Tehreem; Fatima, Laraib
Graphical abstract: Abstract: The poor healing of diabetic wound affects large proportion of human beings by high mortality rate and associated expenditures. Such chronic wounds mainly become problematic due to unavailability of suitable environmental conditions which lead to cell migration, proliferation and uncontrolled inflammation. An ideal dressing should prohibit wound dryness and allow a suitable environment at the injury surface. However, present wound dressing therapeutics lacks the potential to overcome these problems resulting in their limited clinical success. There is a shift research domain from synthetic to natural polymeric materials to overcome issues associated with traditional wound dressings. Many biological organisms' extracted polymers are useful for injury healing due to their ease of availability and various active substances. The naturally occurring polymers mainly polysaccharides and proteins find several attractive applications in the biomedical field.These substances are not only non-toxic but also possess ideal wound dressing characteristics. In this work, the polysaccharides and proteins-based biopolymers utilized in recent years as wound dressing material are discussed. This review will surely provide guidance to researchers in using biopolymers as effective and economical wound dressing material.